- #1

- 230

- 0

## Main Question or Discussion Point

if

[tex] \mu = cos(\theta) [/tex] and [tex] \mu_{0} = cos(\theta_{0}) [/tex]

and

[tex] cos(\pi - \Theta) = \mu_{0}\mu + \sqrt{1-\mu_{0}^{2}}\sqrt{1-\mu^{2}}cos(\phi) [/tex]

Then

[tex] cos(\pi - \Theta) = cos(\theta_{0})cos(\theta) + sin(\theta_{0})sin(\theta)cos(\phi) [/tex]

Is this not correct?

[tex] \mu = cos(\theta) [/tex] and [tex] \mu_{0} = cos(\theta_{0}) [/tex]

and

[tex] cos(\pi - \Theta) = \mu_{0}\mu + \sqrt{1-\mu_{0}^{2}}\sqrt{1-\mu^{2}}cos(\phi) [/tex]

Then

[tex] cos(\pi - \Theta) = cos(\theta_{0})cos(\theta) + sin(\theta_{0})sin(\theta)cos(\phi) [/tex]

Is this not correct?